Populism as a fantasmatic rupture in the post-political order: integrating Laclau with Glynos and Stavrakakis. (2nd July 2016) - Salter, L
ABSTRACT: The recent challenges of populist movements to the 'post-democratic horizon' in Greece and elsewhere have highlighted its possibilities as a political force able to mount a challenge to the technocratic logics of the neoliberal consensus. The theoretical perspective of Ernesto Laclau, which focuses on the rhetorical act of naming 'the people' and extrinsic representative form over intrinsic content, thus becomes increasingly valuable to explore such possibilities and to account for the current ubiquity of populist articulations both here in New Zealand and further afield. However, the need to clarify and iron out any inconsistencies in Laclau's approach also increases, and the main task of this article is to raise the consideration of how it could be supplemented by, and articulated with, the Lacanian psychoanalytic concepts of fantasy and jouissance. Analysis of a selection of John Key's populist articulations in the New Zealand media, and photographs from Trans-Pacific Partnership (TPP) protests, reveal that both forms of populist articulation, while constructing very different visions of 'the people', hinge on the fantasmatic representation of an other; an antagonistic power who steals our enjoyment. However, I conclude that a normative assessment of populist articulations is both possible and necessary.